An ESP Learning Materials for Students of Midwifery - Kadek Heni Oktarina Wisudayanti (EDUVELOP, 2020)
As an international language, English plays an important role as a means of communication. English as a tool and as an opportunity to support the future development. Therefore, English as a crucial subject in almost all education levels. One of term that concern with this condition is English for Spesific Purposes (ESP). This research aimed at developing an ESP learning material for students of Midwifery. This study used Research and Development combine the design by R & D design by Dick and Carey model (2005) and Borg and Gall (2003). The result showed that the learning English could be classified as English for Specific Purpose (ESP). English for Specific Purpose (ESP) is in line with the curricular objectives, which is modelled in terms of standard competency, basic competency and learning indicators. Following the competencies and learning indicators. Therefore, the detailed learning materials would be described in terms of (1) language function, (2) language features, and (3) text structures. Moreover, the result of questionnaire showed the students’ positive responses toward the learning materials. The learning materials were also proven effectively improve students’ speaking abilities after the implementation of the learning materials. The developed learning materials is good for English learning for students of Midwifery because it accomodates the needs of the students in their students teaching and learning process of ESP lesson. Keywords: English for Specific Purposes (ESP); ESP Material: Material Development